2017
DOI: 10.14214/sf.5643
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and sexual reproduction in relict populations of Betula nana

Abstract: Highlights• Genetic diversity parameters and meiotic recombination frequencies in the relict populations were comparable to those from widespread localities.• Contribution of seeds without ovule was very high.• Fully developed seeds germinated better in central populations.• Significant differences of groundwater parameters were observed between relict and central populations. AbstractIn the present study, the impact of geographical isolation and habitat conditions on genetic diversity and sexual reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…High level of genetic variation increases the potential of the species to respond to selective pressure. Previous studies on B. nana showed that endangered central European populations are not genetically extinct compared to widespread localities from Finland and Russia, which may result from rare outcrossing events in long-lived clonal populations (Jadwiszczak et al 2017). Based on RAPD markers, the results reported here show that the populations Abisko, Malbo, Gällivare and Storlien, which are located at the edge of the natural range of B. nana and occupy different habitats, are genetically diverse to varying degrees.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…High level of genetic variation increases the potential of the species to respond to selective pressure. Previous studies on B. nana showed that endangered central European populations are not genetically extinct compared to widespread localities from Finland and Russia, which may result from rare outcrossing events in long-lived clonal populations (Jadwiszczak et al 2017). Based on RAPD markers, the results reported here show that the populations Abisko, Malbo, Gällivare and Storlien, which are located at the edge of the natural range of B. nana and occupy different habitats, are genetically diverse to varying degrees.…”
Section: Discussionmentioning
confidence: 49%
“…Based on this result, it was hypothesised that Poland was either colonised by distinct glacial refugia or haplotype fixation resulted from genetic drift acting strongly in relict populations (Jadwiszczak et al 2012). To protect these sites, studies on genetic parameters and monitoring of genetic diversity have also been conducted in populations occurring in the compact and continuous range of dwarf birch in Fennoscandia (Jadwiszczak et al 2017;Tsuda et al 2017;Borrell et al 2018). Such studies provide the reference material necessary to assess the status of relict populations and develop strategies to protect them.…”
Section: Introductionmentioning
confidence: 99%
“…Although contradictory, such results have been registered for other species, such as Andromeda polifolia (Jacquemart 1998). Most of the studies that follow the reproductive behaviour of glacial relict plant species (Jacquemart 1998, Taylor et al 2002, Chrzanowska et al 2016, Jadwiszczak et al 2017 were performed under laboratory-controlled conditions. In the particular case of L. sibirica, some studies analysed the germination capacity either in situ (Kukk 2003), or under laboratory conditions, from its main distribution area (Siberia) (Fomina 2016), to its western distribution limit (Estonia) (Kukk 2003, Kļaviņa et al 2004, Ilves et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The production of seeds with no embryos is not a rare phenomenon in the birch taxa. For example, the median numbers of empty seeds in B. nana populations have been measured as ranging from 86 to 99 per 100 seeds (Jadwiszczak et al 2017). Seeds without embryos constituted 57.6% of the B. pendula seed set and 58.5% of B. pubescens seed set in northern Sweden (Holm 1994).…”
Section: Pollen and Seed Qualitymentioning
confidence: 99%
“…In our opinion, there are several possible explanations for the reduced germination success of endangered B. humilis. The first explanation is a substantial contribution of empty seeds (without embryo), as was discovered in relict central European localities of dwarf birch (Betula nana L.) (Schwartz and Poschlod 2015;Jadwiszczak et al 2017). Empty seed production can result from a decrease in the quality or quantity of pollen (pollen limitation), which can significantly reduce maternal plants' reproductive success (Knight et al 2005;Balogh and Barrett 2018).…”
Section: Introductionmentioning
confidence: 99%